Comparative Study of Computer Vision Syndrome and Smart Devices among the Employers and Students in College of College of health and Medical Technique of University of Al -Furat Al-Awsat Techniques. Kufa (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Objectives Survey about numbers of students and employers that they were influenced by recurrent using of computers and smart devices, in addition to that, the comparative study performing by knowing of relationship with different and effect on them. Materials And Methods This study was executed on individuals of students and employees during 1 year only (from January 1st 2016 to August 15th 2017) in the College of Health and Medical Technology /kufa in the province of Al-Najaf. It is included in the relation between frequent using of computers and smart devices and another risk factor. Results The results shown significant differences in student’s users of computers and smart devices in which there were little numbers of visions influencing among them in different ages and genders. Utilizing for long periods during days in different purposes yet didn't have a greater effect on users in case of computer vision syndrome according to the employer’s users. Since the preparation of students was having medical glass in male and female and the letter has rated more than the male. In another hand the ages at about (24-32) the using of computers and smart devices was, and the more risk factors among all of them had had greater rates of correlation with the glass wearing in a group of students that they have eye allergy in comparison with the time user. Also these results were shown the superiority of male in comparison with female in using these devices So, from the results mentioned above the convergence in numbers of students that they have vision affects due to employment of these devices in such of ages about [(19-23), (24-32)] in male and female, but the first ages have slightly higher rates than other)] by percentage (50%) of the students that suffer from computer vision syndrome from all proportion, whereas 2nd group of another age has low significant differences in comparison with previous by the percentage closely (36.36%). The employer’s users of computer and smart devices have significant differences (p< 0.05) from the previous results, where it was noticed large numbers of users suffer from problems in their vision due to profuse utilization for long periods of this advice. At the ages (31-40) using for different purposes whether (science, entertaining or both of them) has close correlation with hitting of employers by vision syndrome, where this factor has significant differences in comparison with other risks (p